Emerging Role of Irisin as Metabolic Marker of Peripheral Insulin Resistance - Senghor , K. A. Arul; Renuka P.; Vinodhini , V. M.; Nilofer Sagana M. K. (Novel Research Aspects in Medicine and Medical Science Vol. 9, 2023)
Irisin a recently discovered exercise-induced myokine, found mostly in skeletal muscle and adipose tissue. It functions as a signaling molecule in metabolic regulation and plays an important role in the field of exercise physiology. The males and females have variances in Irisin levels based on hormonal profiles and body composition. Due to substantial effect of Irisin on metabolic syndrome has captivated the interest of researchers and clinicians. The multidimensional function of irisin in coordinating a variety of physiological responses is explored, in particular its impact on energy expenditure, adipose tissue remodeling, and insulin sensitivity. Irisin as a riveting myokine that is triggered by exercise and released from the muscle to support organ and tissue physiology and enhance insulin action by augmenting insulin receptor sensitivity. Understanding the irisin signaling pathways that regulates peripheral up-regulation of insulin activity in humans is crucial.